Pengaruh Implementasi Pembelajaran Berbasis Game Wordwall terhadap Peningkatan Hasil Belajar dan Kemampuan Berpikir Kreatif Siswa - Khoironiya, Fahmi; Herliani, Herliani; Akhmad, Akhmad; Serena, Nelda Anasthasia (Symbiotic: Journal of Biological Education and Science, 2025)
Creative thinking skills encourage students to find new solutions, make scientific predictions, and solve problems based on biological concepts. These abilities include indicators such as fluency, flexibility, originality, and elaboration. Thus, a meaningful learning process is needed and encourages active student involvement. One approach that can be used is the Game Based Learning (GBL) model assisted by Wordwall media, maze-chase type. This study aims to determine the effect of using the GBL model assisted by interactive media on students' learning outcomes and creative thinking skills. The type of research used is Quasi Experimental Design with the form of Nonequivalent Control Group Design. Through purposive sampling technique, a sample of 22 students from class XI-3 (experimental class) and class XI-4 (control class) was obtained. Data were collected through written essay tests (pretest and posttest). The results of data analysis using the t-test showed that the learning outcome test obtained a calculated t value = 7.050 and t table = 2.018, while the creative thinking ability test obtained a calculated t value = 4.923 and t table = 2.018. Because of the calculated t> t table and the significance value <0.05, it can be concluded that the application of the GBL model assisted by the maze-chase type Wordwall media is able to improve the learning outcomes and creative thinking abilities of class XI students at SMA Negeri 5 Samarinda.